Oral care protocol for oral mucositis in HSCT using stabilized 0.02% chlorine dioxide-based products - Mello, Walmyr Ribeiro de; Evangelista, Nara; Marques, Juliana; Gouveia, Roseane Vasconcelos; Seber, Adriana (Brazilian Journal of Transplantation, 2017)
Individuals diagnosed with Acute Myelogenous Leukemia (AML) may present oral manifestations resulting from the disease and manifestations resulting from chemotherapy and radiotherapy treatment. Case Report: Male patient, three years old, diagnosed with refractory Acute Myeloid Leukemia (AML), type 1 diabetes mellitus (DM1) and hypothyroidism. Received unrelated allogeneic hematopoietic stem cell transplant (HSCT). In the control of DM1 continuous infusion therapy of subcutaneous insulin and insulin pump associated with nutritional control were used. Intraoral physical examination was performed on the first day of admission. Protocols from the institution of oral hygiene care and Low Power Laser Therapy (LBP) were prescribed for the control and prevention of oral mucositis (OM). On D+5 with leukocytes=50/mm3 he presented grade II mucositis, inappetence with dysgeusia, leading to the installation of parenteral nutrition. Revised the oral hygiene care protocol due to its low tolerability and adherence, replacing only the 0.12% aqueous chlorhexidine oral rinse with the 0.02% stabilized chlorine dioxide solution, and the lactoperoxidase-based oral humectant gel by oral wetting gel based on 0.08% chlorine dioxide stabilized, maintaining the LBP protocol. On D+7 with leukocytes=40/mm3, OM regressed to grade I with food acceptance and elimination of dysgeusia. On D+13 with leukocyte=280/mm3, MO grade 0. On D+18, date of marrow engraftment, parenteral nutrition was withdrawn and breast milk was accepted again. Conclusions: We concluded that the replacement of the 0.12% aqueous chlorhexidine oral rinse and the lactoperoxidase-based humectant gel that were causing non-adherence to the protocol due to intolerance by the 0.02% stabilized chlorine dioxide-based oral rinse and by Wetting gel based on 0.08% chlorine dioxide stabilized showed greater tolerability and resumption of the protocol, providing reduction and control of the severity of oral mucositis, even in the period of HSCT neutropenia.